P137 Interpretation of plethysmography in healthy young children. (2nd December 2011) - Kirkby, J C; Bonner, R; Lum, S; Bates, P; Morgan, V; Strunk, R; Kirkham, F; Sonnappa, S; Stocks, J
Abstract : Introduction: Plethysmographic lung volumes are the gold standard for identifying restrictive lung defects (reduced TLC), and are useful for delineating obstructive defects (increased RV/TLC).1 Interpretation of these measurements may, however, be limited without appropriate reference equations. The BTS recommend equations by Rosenthal2 (based on white subjects) for children. However, to our knowledge, no ethnic-specific plethysmographic equations have been published for black children, in whom lower spirometric values are known to exist. Aim: To evaluate the appropriateness of plethysmographic reference equations in healthy young children according to ethnic origin. Methods: Healthy children (68 black and 115 white) aged 6–12 yrs underwent plethysmography measurements according to standardised guidelines.1 Results were adjusted for sex and height and expressed as %predicted and z-scores using recommended equations.2 Unpaired t-tests were used to establish ethnic differences. Results: Ethnic differences in lung volumes were dependent on the outcome: Black children had significantly lower FRC (∼6% or 0.3z) and TLC (∼8% or 0.6z), but no significant differences in RV such that their RV/TLC ratio was significantly higher (Abstract P137 table 1 ). In addition, relatively poor agreement between observed vs predicted FRC was seen in healthy white children. To avoid misdiagnosis, the limits of normality (mean±2 SD) need to be adjusted to cater for these discrepancies. These preliminary data suggest that, based on the Rosenthal equations, the lower limit of normal for TLC, (to detect restriction), would be ∼75% predicted (−2.1z) for black children and ∼80% predicted (−1.7z) for white children. For detecting hyperinflation using RV/TLC the upper limit of normal would be ∼148% predicted (2.3z) for black children and ∼135% predicted (1.7z) in white children, whereas for FRC they would be ∼111%predicted (0.4z) and 122% predicted(1.2z) in black and white children respectively. Conclusion: Ethnic differences in lung volumes exist and cannot be accounted for by a simple correction factor. Current paediatric plethysmographic reference equations are not appropriate, and may lead to misdiagnosis unless limits of normality are adjusted. Caution in interpretation is recommended until more appropriate reference equations can be developed. This requires prospective plethysmographic lung volume data collection using standardised protocols in children from different ethnic backgrounds.